Leukemia inhibitory factor impairs structural and neurochemical development of rat visual cortex in vivo - Engelhardt, Maren (Molecular and cellular neuroscience, 2017)
Minipump infusions into visual cortex in vivo at the onset of the critical period have revealed that the proinflammatory cytokine leukemia inhibitory factor (LIF) delays the maturation of thalamocortical projection neurons of the lateral geniculate nucleus, and tecto-thalamic projection neurons of the superior colliculus, and cortical layer IV spiny stellates and layer VI pyramidal neurons. Here, we report that P12-20 LIF infusion inhibits somatic maturation of pyramidal neurons and of all interneuron types in vivo. Likewise, DIV 12-20 LIF treatment in organotypic cultures prevents somatic growth GABA-ergic neurons. Further, while NPY expression is increased in the LIF-infused hemispheres, the expression of parvalbumin mRNA and protein, Kv3.1 mRNA, calbindin D-28k protein, and GAD-65 mRNA, but not of GAD-67 mRNA or calretinin protein is substantially reduced. Also, LIF treatment decreases parvalbumin, Kv3.1, Kv3.2 and GAD-65, but not GAD-67 mRNA expression in OTC. Developing cortical neurons are known to depend on neurotrophins. Indeed, LIF alters neurotrophin mRNA expression, and prevents the growth promoting action of neurotophin-4 in GABA-ergic neurons. The results imply that LIF, by altering neurotrophin expression and/or signaling, could counteract neurotrophin-dependent growth and neurochemical differentiation of cortical neurons.